Genetic Variation and Phylogenetic Analysis of Philippine Scrubfowl (Megapodius cumingii) Based on Mitochondrial NADH Dehydrogenase Subunit 2 (ND2) Gene - Jihan Winarti; I Made Budiarsa; Manap Trianto; I Nengah Kundera; Mursito S. Bialangi; Abdul Ashari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Central Sulawesi is one of the provinces in Indonesia with high avian diversity, including the Philippine scrubfowl (Megapodius cumingii). This species belongs to the family Megapodiidae and is distributed in the Philippines, parts of eastern Borneo, and several small islands in Indonesia. This study aimed to analyze the genetic variation and phylogenetic relationships of Megapodius cumingii from Poat Island based on sequences of the mitochondrial NADH dehydrogenase subunit 2 (ND2) gene. Genomic DNA extracted from blood samples of the Philippine scrubfowl was isolated using the gSYNC™ DNA Extraction Kit (Geneaid), amplified using the Polymerase Chain Reaction (PCR) method with primers L5145 (forward) and H6394 (reverse), and visualized by 1% agarose gel electrophoresis. The PCR products were purified using the QIAquick PCR Purification Kit. Sequence data were analyzed using BLAST for species confirmation, DnaSP v6.12.03 for genetic variation analysis, and MEGA 11 for phylogenetic tree reconstruction using the Maximum Likelihood and Neighbor-Joining methods. The results showed that the 1.072 base pair ND2 gene sequences generated three haplotypes, with a haplotype diversity value of 0.667 and a nucleotide diversity of 0.00249. The nucleotide base composition of the ND2 gene was dominated by A+T (52.03%) compared to G+C (47.95%). Phylogenetic tree reconstruction using both methods produced consistent topologies, in which all Megapodius cumingii samples from Poat Island formed a monophyletic clade with high bootstrap support, indicating strong and stable genetic relationships.